Analisis Proses Pembelajaran Daring Pada Masa Pandemi Covid-19 Di SDN Tondomulyo Jakenan - Ema Agustiana; Muhammad Noor Ahsin; Gunawan Setiadi (WASIS : Jurnal Ilmiah Pendidikan, 2022)
This study aims to describe the process and constraints of online learning during the Covid-19 pandemic in class III SDN Todomulyo Jakenan.This study uses a qualitative method with the type of narrative research. Data collection techniques in this study using observation and interviews with data sources teachers and students. The data analysis technique uses the stages of data reduction, data presentation, and drawing conclusions.Based on observations, it shows that the online learning process during the COVID-19 pandemic at SDN Todomulyo has been carried out well, teachers and students already have the basic facilities needed, this shows readiness to carry out online learning. Online learning causes the delivery of material to be not optimal and less effective. Students who feel bored to the point of not wanting to do the assignment. The solutions to overcome the problems of online learning include teachers continuing to provide guidance and assistance to students.